Development of Escape the Virus Android-based Endless Runner Game with Local High Score and Progressive Level Features - Nadia Rahmawati Asnan; Primandani Arsi; Anugerah Bagus Wijaya (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
The rapid growth of Android-based games has increased the demand for applications that not only provide engaging gameplay mechanics but also incorporate features that support user experience. However, previous studies on endless runner games have primarily focused on core gameplay mechanics and system functionality, with limited attention to supporting features related to player motivation and engagement. Therefore, this study aims to design and develop Escape the Virus, a 2D Android-based endless runner game, and evaluate user responses to the implementation of a local high score system and a progressive level mechanism. This study employed a Research and Development (R&D) approach using the Multimedia Development Life Cycle (MDLC) method, which consists of the concept, design, material collecting, assembly, testing, and distribution stages. The game was developed using Unity with an obstacle avoidance concept and a scoring system based on the player's ability to avoid obstacles. System testing was conducted using Black Box Testing, while user evaluation involved 100 respondents through a Likert-scale questionnaire. The testing results indicated that all game features functioned according to the designed specifications. User evaluation showed positive responses, with average scores of 4.22 for active participation, 4.26 for playing motivation, and 4.21 for level progression. In addition, the local high score system and progressive level mechanism received positive responses from users and were perceived as features that support motivation and engagement during gameplay. These findings indicate that the integration of supporting features in an Android-based endless runner game was positively received by users during the evaluation process.